HEALTHY WELLNESS LIFESTYLE: A KEY FACTOR FOR DEVELOPING BETTER COPING SKILLS AMONG HIGHER SECONDARY SCHOOL STUDENTS OF KERALA - NOORA ABDUL KADER (International Journal of Advanced Research, 2014)
Our life is surrounded by many problems which are not always possible to avoid. However we should have some sort of control on how to deal or cope with these problems. More or less, we could keep a balance of our own emotional state inspite of losing the balance completely. The present study investigated the effect of Lifestyle Factors on Coping Skills among Higher Secondary School students of Kerala. A sample of 100 Higher Secondary School students was selected from the two districts of Kerala through stratified random sampling technique. ANOVA, Sheffe‟s test of multiple comparison and Mean difference Analysis were the statistical techniques used in the present study. The analysis of the study revealed that there exists significant effect of Lifestyle Factors on coping among Higher Secondary School students. Significant difference is found in the mean scores of Lifestyle Factors and Coping Skills for the subsamples based on gender and type of institution. There occurs great danger in developing ineffective coping strategies for dealing with stress such that they may become habitual or even addictive. The present study paves way for the teachers and parents to mould wellness lifestyle among Higher Secondary School students for developing better coping strategies